1976
DOI: 10.1007/bf01220632
|View full text |Cite
|
Sign up to set email alerts
|

Role of insulin resistance in adipose tissue and liver in the pathogenesis of endogenous hypertriglyceridaemia in man

Abstract: Studies were performed to evaluate the relative importance of enhanced adipose tissue lipolysis and increased insulin levels in modulating hepatic VLDL production in patients with endogenous hypertriglyceridaemia. Eight control subjects and nine patients with hypertriglyceridaemia were investigated. The latter group comprised four patients with idiopathic hypertriglyceridaemia, three maturity onset diabetics, and two siblings with diabetic lipodystrophy. Each individual's plasma VLDL was selectively labelled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
112
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(116 citation statements)
references
References 37 publications
3
112
0
1
Order By: Relevance
“…In contrast, apoB levels were correlated with NEFAs only, consistent with findings that plasma VLDL apoB turnover is correlated with plasma NEFA flux but not with plasma insulin. 18 Although impaired clearance by lipoprotein lipase could account for the association of elevated triglyceride levels with impaired insulin-mediated NEFA suppression, such a mechanism would not account for the correlation of postload NEFAs with apoB, which is not cleared by lipoprotein lipase. Experimental studies have demonstrated that elevated NEFA levels increase triglyceride synthesis and apoB secretion by hepatocytes in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, apoB levels were correlated with NEFAs only, consistent with findings that plasma VLDL apoB turnover is correlated with plasma NEFA flux but not with plasma insulin. 18 Although impaired clearance by lipoprotein lipase could account for the association of elevated triglyceride levels with impaired insulin-mediated NEFA suppression, such a mechanism would not account for the correlation of postload NEFAs with apoB, which is not cleared by lipoprotein lipase. Experimental studies have demonstrated that elevated NEFA levels increase triglyceride synthesis and apoB secretion by hepatocytes in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…FFA, total cholesterol, LDL cholesterol and TG concentrations in the blood are increased in obesity (Considine et al, (Kissebah et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cytokines released from fat cells, including leptin, TNF-α and IL-6, are closely related to insulin resistance (Weigle, 1994;Nielsen and Jensen, 1997;Kissebah et al, 1976), and they are known as major causes for diabetes (Mohamed-Ali et al, 1997;Mohamed-Ali et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Increased portal FFA availability may result in reduced hepatic insulin clearance, 2,3 increased hepatic glucose production 4 and increased very-low-density-lipoprotein (VLDL) triglyceride synthesis. 5 All these abnormalities provide a conceptual rationale for examining the relationship between various metabolic disturbances and adipose tissue distribution.…”
Section: Introductionmentioning
confidence: 99%